Traditional ecological knowledge to traditional foods: The path to maintaining food sovereignty in Hutsulshchyna - Fontana, Nina M.; Pasailiuk, Mariia V.; Pohribnyi, Oleh (Frontiers in Sustainable Food Systems, 2022)
The various ecosystems of the Carpathian Mountains spanning Europe, are a rich refuge for culturally important, endemic plant species as well as large carnivores. These biologically diverse landscapes are a principal source of subsistence to 16 million people, including various ethnographic groups. This paper focuses on a case study involving Hutsul communities, an ethnographic group of traditional pastoral highlanders, in the Southeastern Carpathian Mountains of Ukraine. Given ecosystem, climatic, and cultural challenges, especially the rise of illegal logging, commercial harvesting, increased frequencies of flooding, and now a war, Hutsul communities face extensive threats to maintaining socio-ecological resilience in the region. A contributing factor to the region’s centuries-long resilience is TEK upholding food sovereignty as seen through traditional foods derived from Carpathian ecosystems. Traditional ecological knowledge (TEK) is as a dynamic, generationally-held knowledge base, where language, gathering practices, landscape and culture inform livelihoods. In this article, we seek to answer the following series of questions within Hutsul communities: 1) What does TEK look like in the region? 2) What are the regional environmental challenges? 3) Given these challenges, what are coping mechanisms and adaptive strategies grounded in TEK, ensuring a resilient food sovereign system? Mixed methodologies guided by community-based participatory action research methods (CBPAR) between 2017-2019 provide a rich, context-driven perspective on regional TEK. Radiating out from the historical, cultural Hutsul capital, Verkhovyna, 40 experts (including knowledge holders, elders, foresters, community members) were interviewed in 8 neighboring villages. We, along with Hutsul experts, explore the presence of traditional ecological knowledge (TEK) in Hutsulshchyna by identifying 108 culturally important species including wild plants (74 species), cultivated plants (23 species), fungi (9 species) and lichens (2 species); these species are gathered in 10 habitats with varying degrees of human interaction. We analyze species’ presence in traditional foods in the past and present day, as well as contextualize regional environmental challenges impacting TEK practices, and responses to these challenges (coping mechanisms and adaptive strategies). Despite various regional challenges, we conclude that the strong presence of TEK provides a resilient foundation for supporting food sovereignty as seen through the presence of traditional foods.